Non-participation in mammographic screening - experiences of women from a region in Sweden - Maria Norfjord van Zyl; Sharareh Akhavan; Per Tillgren; Margareta Asp (BMC, 2020)
Abstract Background Understanding women's life conditions regarding their non-participation in different health-promoting and disease-preventing activities is important as it may draw attention to potential areas for improvement in the healthcare sector. Mammographic screening, a disease-preventing service, facilitates early detection of any potential malignancies and consequently prompts initiation of treatment. The reasons for non-participation in mammographic screening can be understood from different perspectives, such as socioeconomic and lifestyle-related determinants of health. This study aims to gain a deeper understanding of women's experiences and perceptions about non-participation in mammographic screening in a Swedish region with a single mammographic facility. Methods Data from individual semi-structured interviews, conducted in 2018 with eleven women between the ages of 48 and 73, were analysed by a qualitative content analysis. Results The findings reveal three main categories: 1) doubts regarding mammographic screening and its organisation, 2) sense and sensibility in the decision to refrain from mammographic screening, and 3) dependency and options. These three categories indicate aspects, such as the individual's life situation, accessibility to the offered service, and the flexibility of the healthcare system, that need to be considered to improve the organisation of mammographic screening. Conclusion Listening to the women's voices regarding their experiences and perceptions about mammographic screening is important as individual characteristics and social circumstances interact with healthcare and affect the degree of participation.